From invention to progress: Energy technology innovation and sustainable development in OECD economies - Khatib Ahmad Khan; Waheed Ahmad; Azeem Oluwaseyi Zubair; Mohammad Subhan; Muhammad Ibrahim Shah (PLoS ONE, 2025)
In the era of Industry 4.0, the advancement in energy technology has taken centre stage to mitigate climate change and promote sustainable development. Ever since the adoption of the United Nations SDGs in 2015, different regions and countries have been moving to achieve these targets by implementing various mechanisms. The OECD is one such region where aggressive funding towards equipment with high energy efficiency and the advancement of technologies for producing and consuming renewable energy are provided to advance towards sustainable development. Given the economic significance of the aforementioned countries, this study evaluates the influence of energy technology innovation on sustainable development in OECD countries. Our research focuses on energy technology innovation, which we measure through the energy technology R&D budget. In addition to energy technology innovation, we consider several other control variables such as state fragility index, financial development and foreign direct investment. In order to achieve the aforementioned goal, we utilize advanced econometric modelling methods of the second generation. These techniques encompass a CSD test, unit root tests, cointegration test, and CS-ARDL model. The result from CS-ARDL suggests that energy technology innovation enhances sustainable development in the short and long run. State fragility is shown to influence sustainable development negatively and significantly. The role of financial development as well as foreign direct investment, is found to be favourable for sustainable development. Based on the outcome, it is recommended that countries of this region significantly increase investment in energy technology, enhance financial development and encourage foreign direct investment along with tackling the fragility of these nations to boost sustainable development.